Factors associated with adherence to guidelines in cancer pain management among adult patients evaluated at oncology unit, in the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia - Kibret, Anteneh Ayelign; Wolde, Haileab Fekadu; Molla, Meseret Derbew; Aragie, Hailu; Getnet Adugna, Dagnew; Tafesse, Ephrem; Melese, Endalkachew Belayneh; Worku, Yilkal Belete; Belay, Daniel Gashaneh (Frontiers in Pain Research, 2022)
Abstract Introduction: Cancer pain is one of the most important deleterious and distressing symptoms suffered by cancer patients which disturb their quality of life especially in the last part of their life. Alleviating pain is a primary goal of prognosis of cancer pain management and pain symptoms must be prevented, treated as a priority, and considered an independent part of cancer management. Despite the presence of guidelines for cancer pain management, many cancer patients are still under treatment. Therefore, this study aimed to assess the prevalence of inadequacy management of cancer pain and associated factors among adult patients evaluated at the oncology unit. Methods: An institution-based cross-sectional study was conducted from January and March 2021. A systematic random sampling technique was used to select a total of 384 participants. The data were collected then entered using EPI DATA version 3.1 and exported to the STATA 14 for analysis. Adjusted odds ratio (AOR) with a 95% confidence interval and having p-value < 0.05 from the multivariable analysis were considered to have a significant association with the outcome. Results: The prevalence of inadequacy management of cancer pain among adult patients in this study was 21.35% (95%CI: 17.53, 25.76). Patients who were not married [AOR =2.2; 95%CI: 1.15, 4.19], who knows their diagnosis before four months ago [AOR =0.53; 95%CI: 0.26, 0.96], who have metastasis CA [AOR =3.76; 95%CI: 1.83, 7.72], being stage III and IV patients [AOR =3.21; 95%CI: 1.64, 7.93] and [AOR =1.63; 95%CI: 1.09, 5.81] respectively had a significant association to have inadequacy of management of cancer pain. Conclusion: The prevalence of inadequate cancer pain management among adult cancer patients in UoGCSH Northwest Ethiopia is relatively low as compared with other studies. Factors such as; patients who were not married, who have metastasis, and being stage III and IV cancer patients had a significant positive association to have inadequate management of cancer pain management. The hospital should develop guidelines and drug use policies specifically for cancer-related pain (CRP) management, and in-service training regarding CRP management should be given to health care providers who are working in a cancer center.